Optimization of RG1-VLP vaccine performance in mice with novel TLR4 agonists. Issue 2 (8th January 2021) - Zacharia, Athina; Harberts, Erin; Valencia, Sarah M.; Myers, Breana; Sanders, Chelsea; Jain, Akshay; Larson, Nicholas R.; Middaugh, C. Russell; Picking, William D.; Difilippantonio, Simone; Kirnbauer, Reinhard; Roden, Richard B.; et al.
Highlights: BECC TLR4L compound added to Alhydrogel improves humoral responses to RG1-VLP vaccine. VLP dose-sparing and reduction in injection frequency were achieved with addition of BECC. Long-lasting effects on HPV-L1 Ab response induced with BECC compound. Abstract: Current human papilloma virus (HPV) vaccines provide substantial protection against the most common HPV types responsible for oral and anogenital cancers, but many circulating cancer-causing types remain that lack vaccine coverage. The novel RG1-VLP (virus-like particle) vaccine candidate utilizes the HPV16-L1 subunit as a backbone to display an inserted HPV16-L2 17–36 a.a. "RG1" epitope; the L2 RG1 epitope is conserved across many HPV types and the generation of cross-neutralizing antibodies (Abs) against which has been demonstrated. In an effort to heighten the immunogenicity of the RG1-VLP vaccine, we compared in BALB/c mice adjuvant formulations consisting of novel bacterial enzymatic combinatorial chemistry (BECC)-derived toll-like receptor 4 (TLR4) agonists and the aluminum hydroxide adjuvant Alhydrogel. In the presence of BECC molecules, consistent improvements in the magnitude of Ab responses to both HPV16-L1 and the L2 RG1 epitope were observed compared to Alhydrogel alone. Furthermore, neutralizing titers to HPV16 as well as cross-neutralization of pseudovirion (PsV) types HPV18 and HPV39 were augmented in the presence of BECC agonists as well. Levels of L1 and L2-specific Abs were achieved after two vaccinations with BECC/Alhydrogel adjuvant that were equivalent to or greater than levels achieved with 3 vaccinations with Alhydrogel alone, indicating that the presence of BECC molecules resulted in accelerated immune responses that could allow for a decreased dose schedule for VLP-based HPV vaccines. In addition, dose-sparing studies indicated that adjuvantation with BECC/Alhydrogel allowed for a 75% reduction in antigen dose while still retaining equivalent magnitudes of responses to the full VLP dose with Alhydrogel. These data suggest that adjuvant optimization of HPV VLP-based vaccines can lead to rapid immunity requiring fewer boosts, dose-sparing of VLPs expensive to produce, and the establishment of a longer-lasting humoral immunity.